PELATIHAN PUBLIC SPEAKING BAGI SISWA DI NAWATIWAT SCHOOL, THAILAND - Ibdalsyah; Dewi Anggrayni; Desi Hasbiah; Kurnia Nur Khodijah; Shabrina Khairani Hanifa (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2026)
Public speaking skills are essential competencies that support students’ communication abilities and self-confidence in the learning process. However, many students still experience difficulties when speaking in public, such as nervousness, lack of confidence, and limited practical experience. Therefore, this Community Service Program (Pengabdian kepada Masyarakat/PKM) was conducted to improve students’ public speaking skills at Naratiwat School, Thailand. The program employed an educational and participatory approach through material delivery, speaking practice, simulations, as well as discussion and reflection sessions. The implementation of the program showed positive results, as indicated by increased student confidence, more active participation, and improved oral communication skills. Students who were initially passive began to demonstrate greater courage in expressing opinions and speaking in front of an audience. In addition, participants showed improved understanding of basic public speaking techniques, including content mastery, voice intonation, body language, and eye contact with the audience. The results indicate that public speaking training is an effective strategy for supporting the development of students’ communication skills in the school environment. Furthermore, this program has the potential to be developed sustainably as part of efforts to enhance learning quality and prepare students to face future academic and social challenges.